The Influence of K-Pop Idol Brand Ambassadors and Brand Images on the Buying Interest of Tokopedia E-Commerce Users (Survey on Office Employees, Tugu Utara Village, North Jakarta) - Kuhu, Silke Esmeralda; Nuraryo, Imam (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to analyze the influence of brand ambassadors and brand image on purchase intention among Tokopedia users, with a mediating variable, in the Tugu Utara Village Office (North Jakarta). The phenomenon of using public figures, particularly K-Pop idols, as a marketing strategy has become increasingly prevalent to attract consumer attention and build a strong brand image. This research adopts a quantitative approach with a survey method. The sample was selected using purposive sampling from Tokopedia users who are aware of and exposed to promotions involving K-Pop idol brand ambassadors. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The analysis results show that brand ambassadors have a positive and significant effect on purchase intention, and brand image also has a positive and significant effect on purchase intention. The findings highlight that choosing a brand ambassador who aligns with the brand image and has relevant appeal to the target market can enhance consumer purchase intention. In addition, a positive, consistent, and distinctive brand image strengthens consumer trust and influences purchase intention. The study recommends that Tokopedia continue to optimize the synergy between brand ambassadors and brand image through creative, relevant, and sustainable marketing communication strategies.